2017
DOI: 10.1371/journal.pone.0179225
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric properties of knee-specific body-perception questionnaire in people with knee osteoarthritis: The Fremantle Knee Awareness Questionnaire

Abstract: BackgroundRecent systematic reviews have demonstrated that pain associated with knee osteoarthritis (OA) is a complex phenomenon that involves various contributors. People with knee OA exhibit symptoms of impaired body-perception, including reduced tactile acuity, impairments in limb laterality recognition, and degraded proprioceptive acuity. The Fremantle Back Awareness Questionnaire (FreBAQ) was developed to assess body-perception specific to the back in people with chronic low back pain. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 54 publications
12
67
2
Order By: Relevance
“…A graphical distribution of included studies grouped by clinical conditions examined is shown in Figure 3. Twenty-five studies (Grod and Diakow, 2002;Moseley, 2008;Wand et al, 2010Wand et al, , 2013bWand et al, , 2014Wand et al, , 2016Docherty et al, 2012;Lauche et al, 2012a;Valenzuela-Moguillansky, 2013;Hirakawa et al, 2014;Gilpin et al, 2015;Mibu et al, 2015;Nishigami et al, 2015Nishigami et al, , 2017Nishigami et al, , 2018Treleaven and Takasaki, 2015;Beales et al, 2016;Janssens et al, 2017;Moreira et al, 2017;Adamczyk et al, 2018a,b;Ehrenbrusthoff et al, 2018;Magni et al, 2018;Martínez et al, 2018) studies concerned the assessment of SoP dysfunctions, while twelve interventional studies (Barker et al, 2008;Preston and Newport, 2011;Wand et al, 2011Wand et al, , 2013aMorone et al, 2012;Paolucci et al, 2012;Diers et al, 2013;Vetrano et al, 2013;Ryan et al, 2014;Louw et al, 2017;Stanton et al, 2018;Nishigami et al, 2019) investigated the effects of perception-based intervention to reduce pain or to correct perceptual distortions. One study, (Lauche et al, 2012a) was included both in assessment and in intervention studies: it is a qualitative study i...…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A graphical distribution of included studies grouped by clinical conditions examined is shown in Figure 3. Twenty-five studies (Grod and Diakow, 2002;Moseley, 2008;Wand et al, 2010Wand et al, , 2013bWand et al, , 2014Wand et al, , 2016Docherty et al, 2012;Lauche et al, 2012a;Valenzuela-Moguillansky, 2013;Hirakawa et al, 2014;Gilpin et al, 2015;Mibu et al, 2015;Nishigami et al, 2015Nishigami et al, , 2017Nishigami et al, , 2018Treleaven and Takasaki, 2015;Beales et al, 2016;Janssens et al, 2017;Moreira et al, 2017;Adamczyk et al, 2018a,b;Ehrenbrusthoff et al, 2018;Magni et al, 2018;Martínez et al, 2018) studies concerned the assessment of SoP dysfunctions, while twelve interventional studies (Barker et al, 2008;Preston and Newport, 2011;Wand et al, 2011Wand et al, , 2013aMorone et al, 2012;Paolucci et al, 2012;Diers et al, 2013;Vetrano et al, 2013;Ryan et al, 2014;Louw et al, 2017;Stanton et al, 2018;Nishigami et al, 2019) investigated the effects of perception-based intervention to reduce pain or to correct perceptual distortions. One study, (Lauche et al, 2012a) was included both in assessment and in intervention studies: it is a qualitative study i...…”
Section: Study Selectionmentioning
confidence: 99%
“…The distribution of research designs adopted for assessment studies is graphically represented in Figure 5. A conspicuous number of these studies is composed by those validating the Fremantle Back Awareness Questionnaire (FreBAQ) (Wand et al, 2014) and the Fremantle Knee Awareness Questionnaire (FreKAQ) (Nishigami et al, 2017), including validation studies into other languages (Janssens et al, 2017;Ehrenbrusthoff et al, 2018;Nishigami et al, 2018), and cross-sectional or case-control investigations across different clinical samples (Wand et al, 2013aBeales et al, 2016). Figure 6 shows the research designs adopted in the intervention studies included, of which a large part were pre-clinical experimental studies (Diers et al, 2013;Nishigami et al, 2019).…”
Section: Research Designs Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxford knee scores range from 0-48 where higher values indicate less 3 disability. Knee awareness/perception was evaluated using a modified version of the Fremantle 4 Knee Awareness Questionnaire (FreKAQ); scores range from 0-36 with higher scores reflecting 5 less knee awareness (Nishigami et al 2017). Perceived knee size was evaluated using established…”
mentioning
confidence: 99%